A new way of creating cellular polyurethane materials: NIPU foams. (May 2015) - Cornille, Adrien; Dworakowska, Sylwia; Bogdal, Dariusz; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Highlights: Reactivity study of NIPU foaming formulation with various cyclic carbonates and amines. Synthesis of NIPU foam materials. Characterization of foam materials. Study of influence of monomer structure on Tg of networks. Thermo-mechanical study of foam materials. Abstract: This article describes, for the first time, the synthesis of polyurethane foams from the reaction between cyclic carbonates and diamines to yield NonIsocyanate PolyUrethane (NIPU) foams. A poly(methylhydrogenosiloxane) was used as blowing agent to foam the NIPU by reaction with diamines. The raw materials were characterized in order to determine reaction stoichiometry. NIPU foams were characterized by scanning electron microscopy and by measurement of their swelling index and apparent density. The mechanical compression and the recovery of these NIPU foams were analyzed by dynamic mechanical analyses at room temperature. The foams exhibited glass transition temperature between −18 °C and 19 °C and a thermal stability above 300 °C.